Environmental-Friendly Consumption: Measuring the Impact of Lifestyle on Household Carbon Emissions - Alyasa, Faisal Madjid; Hawari, Adam; Syawala, Afif Akbar; Sihaloho, Estro Dariatno Dariatno (Economics and Finance in Indonesia, 2025)
In 2060, Indonesia aims for a clean, emissions-free society. However, achieving this goal requires understanding how lifestyle choices affect household carbon emissions. This study, based on data from the Indonesian Family Life Survey 2014, examines the impact of different diets (plant-based, vegetarian, Mediterranean, full meat-based, and mixed) on carbon emissions. Using Ordinary Least Square Panel Data Regression, the research finds that plant-based and vegetarian diets have a lower carbon footprint compared to mixed and full meat-based diets. The findings suggest that transitioning to more environmentally friendly consumption patterns can help reduce carbon emissions and benefit the environment.